Registered nurses: Who are they and what do they want? - Preston, Alison (Curtin University of Technology, 2005)
Using 1981 and 2001 Census data together with primary data from a 2002 survey of RegisteredNurses in Western Australia, this paper profiles the nurse workforce. Amongst other things thepaper reports on a high level of pay dissatisfaction, particularly amongst younger nurses. Hoursof work also emerges as an important issue, with many RNs employed on a part-time basis andmany more indicating they would prefer to work fewer rather than more hours. The demandsof work and family are shown as impacting on these preferences with 30.6% of RNs reportingdifficulty in balancing these conflicting demands. In the absence of any renewal strategy theaverage age of nursing continues to grow. This age structure will change as RNs retire; onethirdof all RN respondents to the 2002 survey plan on leaving the profession before 2008. Asizeable proportion of those who plan to leave are in the 26-30 age group. The paper shouldsound a number of alarm bells for those engaged in nurse workforce planning.